2021
DOI: 10.52965/001c.24976
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin (FORTICAL, MIACALCIN) for the treatment of vertebral compression fractures

Abstract: Osteoporosis is a common condition affecting the musculoskeletal system. It carries with it increased risks of fracture in many areas of the body, leading to reduced quality of life, limited mobility, and other long-term implications such as chronic pain. Vertebral compression fractures are a common development in patients with osteoporosis. Current treatment options focus on reducing pain; preventative methods are somewhat limited and focus on minimizing risk factors for the development of osteoporosis. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is also used to treat uterine fibroids, to control ovarian stimulation during IVF, and as part of transgender hormone therapy. IN salmon calcitonin (Miacalcin™ or Fortical™) is a peptide approved by the FDA for the treatment of osteoporosis in women over the age of 50 [ 272 ]. Table 4 lists intranasally administered biologics available on the market.…”
Section: Nasally Administered Biologics Currently On the Market And I...mentioning
confidence: 99%
“…It is also used to treat uterine fibroids, to control ovarian stimulation during IVF, and as part of transgender hormone therapy. IN salmon calcitonin (Miacalcin™ or Fortical™) is a peptide approved by the FDA for the treatment of osteoporosis in women over the age of 50 [ 272 ]. Table 4 lists intranasally administered biologics available on the market.…”
Section: Nasally Administered Biologics Currently On the Market And I...mentioning
confidence: 99%
“…At present, minimally invasive treatment is basically adopted, which can provide rapid analgesia, improve vertebral height, shorten patients’ bed time, reduce complications, reduce mortality, and improve the quality of life of patients. [ 6 , 7 ] In cases where there has been a significant improvement following treatment or complete recovery, but there is a possibility of recurrence or worsening, such as in the context of vertebral osteoporotic fractures that have been cured but later reappear as vertebral osteoporotic fractures without the occurrence of new vertebral fractures, this situation is considered a relapse. Vertebral osteoporotic fractures and their relapse may be influenced by genetic regulation, leading to an increased risk of disease occurrence, as well as changes in the maintenance time from recovery to recurrence (MTRR).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of hypocalcemia is positively correlated with the rate of bone resorption, and calcitonin antagonizes the increase in the blood calcium concentration by inhibiting the reabsorption of calcium and phosphorus ions by the renal tubules, thereby reducing the rate of bone resorption ( Copp & Cheney, 1962 ; Hedlund, Hulth, & Johnell, 1983 ). Unlike other anti-OP drugs, calcitonin has the unique advantage of having analgesic effects and can relieve acute and chronic pain caused by OP-related vertebral compression fractures ( Lyritis et al, 1997 ; Knopp-Sihota, Newburn-Cook, Homik, Cummings, & Voaklander, 2012 ; Terashima et al, 2019 ); the mechanism underlying this effect this remains unclear ( Kaneb, Berardino, Hanukaai, Rooney, & Kaye, 2021 ). Previous studies have shown that calcitonin may exert analgesic effects by the modulation of the central nervous system as well as neurotransmitter release and neurophysiology ( Pecile, Ferri, Braga, & Olgiati, 1975 ; Yamamoto, Tachikawa, & Maeno, 1981 ; Laurian et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%